2023
DOI: 10.3390/jcm13010185
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stress Urinary Incontinence and Pelvic Organ Prolapse on Depression, Anxiety, and Insomnia—A Comparative Observational Study

Urszula Kalata,
Andrzej Pomian,
Michał Jarkiewicz
et al.

Abstract: Background: Among pelvic floor disorders (PFDs), overactive bladder is a well-recognized condition affecting mental health. The aim of this study was to assess whether there is a correlation between stress urinary incontinence (SUI), pelvic organ prolapse (POP), and mental health in comparison to control subjects and whether objective or subjective aspects of diseases are responsible for the aforementioned symptoms. Methods: 192 patients with SUI, 271 with symptomatic prolapse (>2 in the POPQ scale), and 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…Large-scale Asian cohort studies have further substantiated the link between depression, anxiety, and SUI, identifying SUI as an independent risk factor for these mental health conditions and highlighting its association with significant work impairments [ 25 ]. These findings are consistent with the initial findings of our study published in 2023 [ 8 ], where we demonstrated the adverse impact of SUI by comparing depression and anxiety scales between patients with pelvic floor disorders and healthy individuals.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Large-scale Asian cohort studies have further substantiated the link between depression, anxiety, and SUI, identifying SUI as an independent risk factor for these mental health conditions and highlighting its association with significant work impairments [ 25 ]. These findings are consistent with the initial findings of our study published in 2023 [ 8 ], where we demonstrated the adverse impact of SUI by comparing depression and anxiety scales between patients with pelvic floor disorders and healthy individuals.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings indicate that individuals diagnosed with PFDs exhibit higher levels of severity in these symptoms, as quantitatively assessed using the Center for Epidemiological Studies Depression Scale (CESD), the State-Trait Anxiety Inventory (STAI), and the Insomnia Severity Index (ISI), compared to individuals without pelvic floor pathology. Drawing a parallel to the findings in women during the postpartum period, our study suggests that patients suffering from SUI and POP might also benefit from psychiatric evaluation and care [8].…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation